On the state-dependent nature of odor perception - Shanahan, Laura K.; Kahnt, Thorsten (Frontiers in Neuroscience, 2022)
The olfactory system—and odor perception by extension—is susceptible to state-dependent influences. This review delves into human behavioral research in this area, and also touches on mechanistic evidence and examples from animal work. The review summarizes studies on the impact of satiety state on olfaction, highlighting the robust effects of food intake on the perceived pleasantness of food odors and olfactory decision-making. The impacts of other behavioral states on olfaction are also discussed. While research in this area is more limited, preliminary evidence suggests that odor perception is altered by circadian state, sleep deprivation, and mood. The flexibility in olfactory function described here can be considered adaptive, as it serves to direct behavior toward stimuli with high state-dependent value.